A systematic review and meta-analysis of the utility of repeated versus single hepatic resection for colorectal cancer liver metastases. Issue 6 (June 2017) - Wurster, Elena F.; Tenckhoff, Solveig; Probst, Pascal; Jensen, Katrin; Dölger, Eva; Knebel, Phillip; Diener, Markus K.; Büchler, Markus W.; Ulrich, Alexis
Abstract: Background: Recurrence of colorectal liver metastases after a first hepatectomy is common (4–48% of patients). This review investigates the utility of repeated hepatic resection of colorectal liver metastases. Methods: A systematic search of the literature was performed in the Cochrane Library, MEDLINE, EMBASE, and trial registers. All studies comparing repeated hepatic resection for colorectal liver metastases with patients who underwent only one hepatectomy were eligible. Outcome criteria were safety parameters and survival rates. Data were analyzed using the random-effects model. Results: In eight observational clinical studies, 450 patients with repeated hepatic resection were compared with 2669 single hepatic resections. Morbidity such as hepatic insufficiency (OR [95% CI] 1.46 [0.69; 3.08], p = 0.32) and biliary leakage and fistula (OR [95% CI] 1.22 [0.80; 1.85], p = 0.35) was comparable between the two groups. Mortality (OR [95% CI] 1.13 [0.46; 2.74], p = 0.79) and overall survival (HR [95% CI] 1.00 [0.63; 1.60], p = 0.99) were not significantly different between the two groups. Discussion: Repeated hepatic resection for colorectal liver metastases is safe in selected patients. A prospective, multicenter high-quality trial or register study of repeated hepatic resection will be required to clarify patient-oriented outcomes such as overall survival and quality of life.